IMPLEMENTASI KEBIJAKAN PERAN SERTA LINGKUNGAN PENDIDIKAN TINGGI BERWAWASAN ANTI NARKOBA DI KOTA SEMARANG - Hilda Marta Suri; Kismartini Kismartini (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2017)
Circulation and drug abuse in Indonesia is a multidimensional and multisectoral problem, all lines of life can be exposed to the dangers of drugs. Not apart from that students or young people are the main target of drug abuse, given the level of emotions that have not been stable so easily affected to abuse drugs. Based on Act No 35 of 2009, the Government established the National Narcotics Agency to tackle the drug problem that became a problem in Indonesia, BNN was given the authority of investigation and investigation of narcotics crime and narcotics precursor. In the effort to prevent abuse and illicit drug trafficking as well as handling of government drug problem to include all components of society both from campus environment and work environment. Based on the Regulatory Chief of BNN No 16 of 2014, a Community Participation Container was established to implement the policy towards the participation of the Higher Education Environment. Technical analysis to obtain data through interview with informant, observation, and supporting document. This research uses Merilee S. Grindle theory which argues that the driving factors of implementation have three main factors, namely policy content and policy environment, then the implementation result can be seen from the impact and change on society. The results of this study indicate that the Implementation of the Policy of the Role of the Environment of Higher Education with Anti-Drugs is quite successful in reducing the number of abuse in Semarang City, but still less than optimal with the decrease of performance, and the level of service provided, resulting in the decreasing interest of the Students to join the Unit Anti-drug duties. The desired changes to the creation of an Anti-Narcotics Based Higher Education Environment. The recommendations are to improve the performance and quality of training and counseling, innovation in order to provide facilities and infrastructure that are in line with community expectations.